2003
DOI: 10.1038/sj.pcan.4500611
|View full text |Cite|
|
Sign up to set email alerts
|

Coxsackie B and adenovirus receptor, integrin and major histocompatibility complex class I expression in human prostate cancer cell lines: implications for gene therapy strategies

Abstract: Gene therapy strategies based on modifying tumour cells using high efficiency adenoviral vectors have shown promise in the clinic. Recently the Coxsackie and adenovirus receptor (CAR) has been shown to mediate adenoviral entry into tumour cells, although previous studies also suggested a role for MHC class I heavy chain. Detailed evaluation of the expression of both CAR and MHC class I in prostate cancer cell lines would have important implications for therapeutic strategies. We have found that, unlike cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…It has become apparent that a major determinant of Ads-mediated gene transfer efficacy is the expression of its primary receptor, CAR, on target cells (47). In order to infect tumor cells efficiently, H101 requires CAR for attachment and α v integrin for internalization (48). In the present study, the expression levels of CAR in the mouse xenograft tumor tissue were increased in the TSA group, and in the TSA and H101 combination group.…”
Section: Discussionsupporting
confidence: 53%
“…It has become apparent that a major determinant of Ads-mediated gene transfer efficacy is the expression of its primary receptor, CAR, on target cells (47). In order to infect tumor cells efficiently, H101 requires CAR for attachment and α v integrin for internalization (48). In the present study, the expression levels of CAR in the mouse xenograft tumor tissue were increased in the TSA group, and in the TSA and H101 combination group.…”
Section: Discussionsupporting
confidence: 53%
“…The infectivity of Ad on different prostate cancer cells has been previously analyzed. 34,35 DU-145 and LNCaP have high CAR, whereas PC-3 has lower cell-surface CAR, which makes it relatively resistant to Ad infection. To circumvent this viral resistance, genetically engineered PC-3 cells have been generated by increasing 35% of CAR-positive cells to 86% CAR-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations on the relative importance of cell surface attachment molecules have shown that CAR expression appears to regulate cell susceptibility to Ad5 transduction much more significantly than a v -integrin expression in a wide range of primary cells and established cell lines. [28][29][30][31][32] However, another report has suggested that transgene expression in Ad5-transduced lung and pancreatic cancer cell lines correlated with levels of b 3 integrin. 20 Furthermore, it has recently been proposed that when cell surface CAR levels are low, a v b 5 can function as an attachment molecule for Ad5 in melanoma and breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%